2022
DOI: 10.4314/jae.v26i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Extension-market linkages on banana commercialisation among smallholder farmers in Meru Region, Kenya

Abstract: The study examined the effect of extension-market linkages on banana commercialisation among smallholder farmers in the Meru region, Kenya. The study sampled 400 farmers from a target population of 288,802 from the Meru region. The Tobit model was used to analyse the effect of extension-market linkages on banana commercialisation. The results revealed that sources of marketing information (Coef. -0.06) had a negative influence on farmers commercialising banana production. The result showed that the reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…Trainings enable agripreneurs to access value-addition information, knowledge, and skills, and also empower them to choose the most profitable form of value-addition activities. This finding is similar to Kirimi et al (2021), who stated that smallholder banana farmers who received training were more likely to utilize banana value addition in Kenya. However, the study concluded that these trainings were inadequate; therefore, awareness creation on value addition could accelerate the adoption process.…”
Section: Determinants Of Decision To Utilize Banana Value Additionsupporting
confidence: 86%
“…Trainings enable agripreneurs to access value-addition information, knowledge, and skills, and also empower them to choose the most profitable form of value-addition activities. This finding is similar to Kirimi et al (2021), who stated that smallholder banana farmers who received training were more likely to utilize banana value addition in Kenya. However, the study concluded that these trainings were inadequate; therefore, awareness creation on value addition could accelerate the adoption process.…”
Section: Determinants Of Decision To Utilize Banana Value Additionsupporting
confidence: 86%
“…It can also enable smallholder farmers to have access to affordable production inputs; hence, this will ensure that farmers are not trapped in low productivity-low return farming activities that lead to food vulnerability. The use of better-quality inputs will improve the ability of smallholder farmers to produce enough marketable surplus and subsequently leads to a better market orientation of goods produced by farmers [14]. The need for developing smallholder market participation has been progressively recognized in efforts to achieve agricultural transformation in developing countries [15].…”
Section: Introductionmentioning
confidence: 99%
“…Having access to land brings economic power, which is usually the basis of social and political power (Muyanga and Jayne, 2014). Land is the mainstay of Kenya's economy since over 80% of the Kenyan population derive their livelihood from agriculture and agriculture contributes about 32.6% to the Gross Domestic Product (Kirimi et al, 2013;Muraoka et al, 2014;KNBS, 2017). Land access can be defined as the process by which people individually or collectively gain rights and opportunities to control and utilize land on a temporary or permanent basis (Khalid et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the country's food security is often attributed to the performance of the agricultural sector and thus, agricultural development is seen as the main pathway to contribute towards food and nutrition security (Verhart et al, 2015). However, the productivity of smallholder farmers is hampered by limited access to land, limited access to credit, low input use, insufficient and poorly maintained market infrastructures, limited/no access to extension services, use of obsolete technology and climate change (Kibet, 2011;Kirimi et al, 2013;Devaux, 2018). Smallscale agriculture tends to be labor-intensive and mostly uses family labor with women providing 43% of the total agricultural labor force (SIDA, 2015).…”
Section: Introductionmentioning
confidence: 99%